Crystal Structures of Alfalfa Caffeoyl Coenzyme A 3-O-Methyltransferase - Ferrer, Jean-Luc (American Society of Plant Biologists, 2005)
Caffeoyl coenzyme A 3-O-methyltransferases (CCoAOMTs) are S-adenosyl-l-methionine-dependent O-methyltransferases (OMTs) involved in lignin biosynthesis. Plant CCoAOMTs belong to a distinct family of OMTs, more closely related to the mammalian catechol OMTs than to other plant OMTs. The crystal structure of alfalfa (Medicago sativa) CCoAOMT in complex with the reaction products S-adenosine-l-homocysteine and feruloyl/sinapoyl CoAs presented here belong to a structurally and mechanistically distinct family of plant small molecule OMTs. These structures provide a new understanding of the substrate preferences and the catalytic mechanism accompanying CCoAOMT-mediated O-methylation of CoA-linked phenylpropanoid substrates.